2018
DOI: 10.1111/jcpe.12999
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peri‐implant marginal tissues around tissue‐level and bone‐level implants in patients with a history of chronic periodontitis

Abstract: Under a rigid supportive therapy, both approaches performed likewise regarding clinical and radiographic parameters for rehabilitation of patients with a history of chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 47 publications
1
37
1
1
Order By: Relevance
“…4,5 A tremendous amount of research data on long-term success of dental implants in periodontally healthy patients exists in the literature. 9,10 However, to date, follow-up studies on clinical and radiographic peri-implant outcomes of SDIs placed in treated cases of generalized aggressive periodontitis (GAgP) remains a gray area. Generally, the microbial niche on dental implants may differ among partially edentulous dentition and completely edentulous patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 A tremendous amount of research data on long-term success of dental implants in periodontally healthy patients exists in the literature. 9,10 However, to date, follow-up studies on clinical and radiographic peri-implant outcomes of SDIs placed in treated cases of generalized aggressive periodontitis (GAgP) remains a gray area. Generally, the microbial niche on dental implants may differ among partially edentulous dentition and completely edentulous patients.…”
Section: Introductionmentioning
confidence: 99%
“…8 There are several studies that evaluated short-and long-term outcomes of dental implants in chronic periodontitis patients. 9,10 However, to date, follow-up studies on clinical and radiographic peri-implant outcomes of SDIs placed in treated cases of generalized aggressive periodontitis (GAgP) remains a gray area.…”
Section: Introductionmentioning
confidence: 99%
“…95%CI: confidence interval of 95% compared with TPI. Only two studies [26,28] reported MBL between implant insertion and loading in this review, both of which revealed less bone resorption of TPI than that of OPI though no significant differences were observed. Further meta-analysis is necessary if more studies on MBL between implant insertion and loading emerge in the future.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, a favorable bone response is associated with a horizontal offset no less than 0.4 mm, according to the review of Atieh et al [46]. Only two studies [26,27] reported the horizontal offset between implant and abutment in this review (one is 0.4mm and another is 0.25mm, 0.4mm or 0.75mm). More data are needed for further analysis.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation